2017
DOI: 10.1016/j.athoracsur.2016.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Lung Perfusion Model to Study Pulmonary Tissue Extracellular Microvesicle Profiles

Abstract: EVLP system provides a platform to understand the kinetics of pulmonary EVs in an isolated fashion. Donor lung recovery may be associated with changes in EV size distribution and proteomic profiles. Pulmonary tissue-specific EV profiling using the EVLP system may provide insights into EV contribution to pulmonary pathologic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In this respect, exosomes and extracellular vesicles (EVs) are attracting great interest. As reported by Vallabhajosyula et al [53] in a study on the perfusate from EVLP lungs, understanding EVs biology may have important diagnostic and therapeutic implications in pulmonary medicine, expanding even more the potentiality of the EVLP model.…”
Section: Discussionmentioning
confidence: 96%
“…In this respect, exosomes and extracellular vesicles (EVs) are attracting great interest. As reported by Vallabhajosyula et al [53] in a study on the perfusate from EVLP lungs, understanding EVs biology may have important diagnostic and therapeutic implications in pulmonary medicine, expanding even more the potentiality of the EVLP model.…”
Section: Discussionmentioning
confidence: 96%
“…Exosomes contain specific proteomic and RNA signatures that reflect the conditional and functional status of their cells of origin (23,28). Recently, we demonstrated that circulating transplant tissue-specific exosome characterization enables noninvasive surveillance of the transplanted solid organ in a time-sensitive, condition-specific manner (25)(26)(27). Thus, we hypothesized that transplanted stem/progenitor cells would release an exosome signal into the peripheral circulation, and characterization of stem/progenitor cell-specific exosomes would enable noninvasive surveillance of the functional activity and conditional status of the transplanted cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells may be an attractive therapeutic strategy owing to their paracrine, immunomodulating, and tissue remodeling properties [115]. Mesenchymal stem cell-derived extracellular vesicles also reportedly have the potential to attenuate lung inflammation in lung IRI [116][117][118][119]. In addition, multilineage-differentiating stress-enduring cells, which are stress-tolerant and nontumorigenic endogenous pluripotent-like stem cells, have been shown to have potential in alleviating pulmonary IRI [120].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%